Structural-parametric model hierarchical relationships of complex information resources management information system state security - Міщенко, А. В. (Science-based technologies, 2015)
It is shown that in organizational management should include a set of tasks of the state of information security management and operational management to - the problem of information security management of aviation infrastructure. Produced adaptation of the main provisions of the general systems theory to the "information security." The bottom line is that the system of "information security" is a hierarchical "complex" system of organizational type (for Bertalanffy) and on the first level of decomposition (functional subsystems) and abstract model - fully - connected graph, whose vertices at the top level of the hierarchy is control subsystem (the public service), at the lower level - functional subsystems.